Effects of Computer-Aided Manufacturing Technology on Precision of Clinical Metal-Free Restorations. (18th October 2015) - Lee, Ki-Hong; Yeo, In-Sung; Wu, Benjamin M.; Yang, Jae-Ho; Han, Jung-Suk; Kim, Sung-Hun; Yi, Yang-Jin; Kwon, Taek-Ka
Abstract : Purpose . The purpose of this study was to investigate the marginal fit of metal-free crowns made by three different computer-aided design/computer-aided manufacturing (CAD/CAM) systems. Materials and Methods . The maxillary left first premolar of a dentiform was prepared for all-ceramic crown restoration. Thirty all-ceramic premolar crowns were made, ten each manufactured by the Lava system, Cercon, and Cerec. Ten metal ceramic gold (MCG) crowns served as control. The marginal gap of each sample was measured under a stereoscopic microscope at 75x magnification after cementation. One-way ANOVA and the Duncan's post hoc test were used for data analysis at the significance level of 0.05. Results . The mean (standard deviation) marginal gaps were 70.5 (34.4)  μ m for the MCG crowns, 87.2 (22.8)  μ m for Lava, 58.5 (17.6)  μ m for Cercon, and 72.3 (30.8)  μ m for Cerec. There were no significant differences in the marginal fit among the groups except that the Cercon crowns had significantly smaller marginal gaps than the Lava crowns( P < 0.001 ) .   Conclusions . Within the limitation of this study, all the metal-free restorations made by the digital CAD/CAM systems had clinically acceptable marginal accuracy.